ITPA gene variant may protect against anemia induced during pegylated interferon alfa and ribavirin combination treatment in Ukrainian patients with chronic hepatitis C - Kucherenko, A.; Pampukha, V.; Bobrova, I.; Moroz, L.; Livshits, L. (Цитология и генетика, 2015)
The aim of this study was to clarify the association between the inosine triphosphate pyrophosphatase (ITPA) gene variants and PEG-IFNα/RBV combination treatment induced anemia in chronic hepatitis C (CHC) Ukrainian patients. The data were collected from 80 CHC patients with HCV genotype 1 infection. All study participants received standard doses of PEG-IFNα and RBV. According to the Hb level changes patients were distributed into: case group—42 patients with combination treatment induced anemia, and control group—38 patients with no signs of anemia. Genotyping for ITPA gene rs1127354 and rs7270101 variants was performed using PCR followed by RFLP assay. Fisher’s exact test was used to estimate the difference in genotype and allelic distribution. Distribution of rs7270101 genotypes was not significantly different between groups of CHC patients with RBV-induced anemia and without it. The frequency of rs1127354 A allele carriers was significantly higher (P < 0.05) in group of CHC patients without anemia (23.7%) comparing to the group of patients with anemia (7.3%). The respective allele frequency in control group (13.2%) was almost 3-fold higher (P < 0.05) comparing to the case group (4.9%). Significant association of ITPA gene rs1127354 with protection against RBV-induced hemolytic anemia was found in Ukrainian patients with CHC infection. Rs1127354 variant may assist as a pharmacogenetic marker in HCV antiviral therapy correction for side effect avoidance.